2008
DOI: 10.1063/1.2839622
|View full text |Cite
|
Sign up to set email alerts
|

Aanalytical calculation of rotor losses in high-speed permanent magnet synchronous motor at different load conditions

Abstract: In this paper, the rotor losses in the high-speed permanent magnet (PM) synchronous motor are discussed. In particular, the influence of different load conditions is highlighted in developed PM synchronous motor. On the basis of analytical field analysis, two-dimensional fast Fourier transformation, and the Poynting theorem, the flux harmonics and rotor losses are predicted and validated by finite element method. Moreover, the difference of rotor losses between the motor with rated- and overload conditions is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In order to generate sinusoidal air-gap magnetic field waveform, improve the torque and radial suspension force density, a novel BPMSM with Halbach magnetized rotor is proposed in this paper. The suspension operation mechanism is analysed in detail [42]- [45]. The mathematical models of the radial suspension force are introduced.…”
Section: Magnetic Bearings (Mbs) Are a New Type Of High Performancementioning
confidence: 99%
“…In order to generate sinusoidal air-gap magnetic field waveform, improve the torque and radial suspension force density, a novel BPMSM with Halbach magnetized rotor is proposed in this paper. The suspension operation mechanism is analysed in detail [42]- [45]. The mathematical models of the radial suspension force are introduced.…”
Section: Magnetic Bearings (Mbs) Are a New Type Of High Performancementioning
confidence: 99%
“…H L · · · · · · · · · · · · · · · · · · · · · (8) where N z is the mesh division in the axial direction (N z = 10), h k is the dimension of the mesh element α in the axial direction, and H L is the lamination thickness. The same calculation applies for the tangential component B t,β , but the axial component B z,β is supposed negligible and is not considered in the hysteresis loss calculation for matter of consistency with the 2D nature of the Steinmetz equations.…”
Section: Calculation Of the Hysteresis Lossesmentioning
confidence: 99%
“…E-mail: ngmthao @toyota-ti.ac.jp * Toyota Technological Institute 2-12-1, Hisakata, Tenpaku-ku, Nagoya, Aichi 468-8511, Japan IPMSM, it has been found that the iron loss increase caused by PWM primarily concerns eddy current loss, with the worst impact on magnets (7) . Furthermore, an analytical model has been developed to evaluate the impact of the load on the rotor iron losses of a high-speed permanent magnet synchronous motor (PMSM) (8) ; this research showed that the load can sensibly increase the rotor iron losses. Impacts of PWM voltage modulation index on motor iron losses in only the no-load condition were shown in (9) (10) .…”
Section: Introductionmentioning
confidence: 99%